Exploring the Perceptions of Moroccan EFL Teachers Towards Task-Based Language Learning - Mohammed Mettar (Indonesian TESOL Journal, 2021)
Moroccan students do not have many opportunities to use English outside the classroom setting. The adoption of task-based language learning (TBLL) is deemed to be an appropriate language instructional method for the Moroccan EFL context. Hence, teachers are explicitly urged in the official Moroccan English language guidelines documents to adopt tasks in their teaching practices. However, no known empirical research has been conducted to investigate teachers’ perceptions and use of TBLL. To fill this gap, this study attempted to investigate high school EFL instructors’ familiarity with TBLL and their views on the use of tasks in their classrooms. An online survey provided quantitative data from 90 participants. Results showed that although Moroccan EFL teachers have a good understanding of the key concepts of this approach, their use of tasks is limited. Lack of task-based materials, large class sizes, and students’ use of their mother tongue to complete the task are identified as the main obstacles facing a high level of use of tasks in teachers’ classroom practices. Several implications for the successful integration of TBLL in the Moroccan EFL context are suggested at the end of the article.